Measurement of thermophysical properties coupled with LCA assessment for the optimization of a historical building retrofit. (October 2015) - Bortolin, A; Bison, P; Cadelano, G; Ferrarini, G; Fortuna, S
Abstract: Historical buildings are a significant part of the Italian building stock and, in most cases, need deep refurbishment interventions to reach the energy criteria required by the current standards. A workflow that integrates on-site surveys and building modeling is mandatory to obtain effective energy saving measures. This work describes the analysis and modeling of the San Vito alla Rivera church, a XIV century building that was damaged during 2009 L'Aquila earthquake, suffering a partial collapse of the façade and of the roof. The latter was selected for a complete restoration that could improve its thermal performance while maintaining, as much as possible, the original structure. Several elements of the roof were collected in situ in order to measure, in laboratory, its thermophysical properties applying standard techniques and alternative methods based on infrared thermography. The accurate characterization of the materials was the starting point for the estimation of the environmental impact of the retrofit aimed to reach a defined thermal transmittance. A model of the building was created with TRNSYS software to calculate the energy consumption before and after the intervention. A Life Cycle Assessment (LCA) analysis was conducted on different insulation materials to determine the one with the lowest impact.